The importance of hydrogen sulfide as a systemic priming agent in strawberry plants grown under key abiotic stress factors - Christou, Anastasis; Papadopoulos, Ioannis; Fotopoulos, Vasileios; Manganaris, George A. (My University, 2011)
Hydrogen sulfide (H2S) is an endogenous gasotransmitter which has been recently found to playa major signaling role in response to abiotic stress factors. In the present study we tested whether hydroponic pre-treatment of strawberry (Fragaria x ananassa cv. Camarosa) roots to a H2S donor, NaHS (10 mM for 48 h) could induce long lasting priming effects and tolerance to subsequent exposure to 100 mM NaCI or 10% (w/v) PEG-6000 for 7 d, as well as to heat stress (42° C) applied for 8 h. This task was undertaken by employing a variety of physiological, biochemical and molecular approaches. Hydrogen sulfide pre-treatment of roots resulted in significantly increased leaf chlorophyll fluorescence, stomatal conductance and relative leaf water content as well as reduced ion leakage and lipid peroxidation levels in comparison with plants directly subjected to salt, PEG and heat stress, suggesting a systemic mitigating effect of H2S pre-treatment to cellular damage derived from abiotic stress factors. In addition, root pre-treatment resulted in the minimization of oxidative and nitrosative stress in strawberry plants, manifested via the reduced de novo synthesis of NO and H202 in leaves and the maintenance of high ascorbate and glutathione redox states following subsequent salt and hyperosmotic stresses. Quantitative real-time RT-PCR data examining antioxidant, transcription factor, heat shock protein and ion transporter gene expression levels suggest that H2S plays a key role in the regulation of multiple transcriptional pathways. Our results indicate that H2S pre-treated plants managed to overcome the deleterious effects of salt, heat and hyperosmotic stress, by controlling oxidative and nitrosative cellular damage mainly through increased performance of antioxidant mechanism, thus proposing a novel role for H2S in plant priming.